2019
DOI: 10.1111/jvec.12334
|View full text |Cite
|
Sign up to set email alerts
|

Tick species establishment in Oklahoma County, Oklahoma, U.S.A., identified by seasonal sampling in residential and non‐residential sites

Abstract: In recent years, human tick‐borne disease occurrence has risen in Oklahoma, U.S.A., but year‐round data on tick presence in frequently used recreational areas is not widely available. In this study, ticks were collected monthly for one year at residential and non‐residential sites in a suburban area of Oklahoma County, OK, U.S.A. At each trapping site, dry ice traps were used in both woodland and grassland areas and fabric tick drags were used in grassland areas. Four species were collected from each park: Amb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 34 publications
3
9
1
Order By: Relevance
“…The questing activity of the three predominant tick species peaked once during the spring and summer months of each of the study year (Figs 4-6), and a distinct unimodal phenology for all life-stages and tick species is clearly evident. This finding is similar to Small et al [13], wherein a unimodal distribution for A. americanum, D. variabilis and I. scapularis were found. However, their study was conducted over a single 12-month period and ticks were largely collected using CO 2 traps and therefore any comparisons during the interannual periods cannot be made.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The questing activity of the three predominant tick species peaked once during the spring and summer months of each of the study year (Figs 4-6), and a distinct unimodal phenology for all life-stages and tick species is clearly evident. This finding is similar to Small et al [13], wherein a unimodal distribution for A. americanum, D. variabilis and I. scapularis were found. However, their study was conducted over a single 12-month period and ticks were largely collected using CO 2 traps and therefore any comparisons during the interannual periods cannot be made.…”
Section: Discussionsupporting
confidence: 92%
“…However, the types of ticks prevalent in the area and their activity periods was not fully known. Questing tick species diversity noted in this study is consistent with other studies conducted over the years in this broad region [13,19,20,[35][36][37] although, the number of A. maculatum adults collected in the present study is higher than previously reported from areas closer to the study site [23,37].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, risk of exposure is impacted by changes in the interface between developed and undeveloped landscapes, such as occurs in suburban areas. Populations of A. americanum can also be found in planned green spaces within the urban environment [42] and in residential suburban areas [43]. As dogs move with their owners in and out of these areas, their risk of exposure to ticks may change.…”
Section: Highmentioning
confidence: 99%